A long-term self-managed handwriting intervention for people with Parkinson's disease: results from the control group of a phase II randomized controlled trial. (December 2017) - Collett, Johnny; Franssen, Marloes; Winward, Charlotte; Izadi, Hooshang; Meaney, Andy; Mahmoud, Wala; Bogdanovic, Marko; Tims, Martin; Wade, Derick; Dawes, Helen
Objective: To report on the control group of a trial primarily designed to investigate exercise for improving mobility in people with Parkinson's disease (pwP). The control group undertook a handwriting intervention to control for attention and time spent practising a specific activity. Design: Secondary analysis of a two-arm parallel phase II randomized controlled trial with blind assessment. Setting: Community. Participants: PwP able to walk ⩾100 m and with no contraindication to exercise were recruited from the Thames Valley, UK, and randomized (1:1) to exercise or handwriting, via a concealed computer-generated list. Intervention: Handwriting was undertaken at home and exercise in community facilities; both were delivered through workbooks with monthly support visits and involved practice for 1 hour, twice weekly, over a period of six months. Main measures: Handwriting was assessed, at baseline, 3, 6 and 12 months, using a pangram giving writing speed, amplitude (area) and progressive reduction in amplitude (ratio). The Movement Disorder Society (MDS)–Unified Parkinson's Disease Rating Scale (UPDRS) item 2.7 measured self-reported handwriting deficits. Results: In all, 105 pwP were recruited (analysed: n   =  51 handwriting, n   =  54 exercise). A total of 40 pwP adhered to the handwriting programme, most completing ⩾1 session/week. Moderate effects were found for amplitude (total area: d  = 0.32; 95% confidence interval (CI): −0.11 to 0.7; P  = 0.13) in favour of handwriting over a period of12 months; effects for writing speed and ratio parameters were small ≤0.11. Self-reported handwriting difficulties also favoured handwriting (UPDRS 2.7: odds ratio (OR) = 0.55; 95% CI: 0.34 to 0.91; P  = 0.02). No adverse effects were reported. Conclusion: PwP generally adhere to self-directed home handwriting which may provide benefit with minimal risk. Encouraging effects were found in writing amplitude and, moreover, perceived ability.